Perception of the new post graduate students of anaesthesiology about the speciality - a questionnaire based cross-sectional survey - Bhar, Sudeshna; De, Anisha; Bhar, Debasish; Bhattacharyya, Chiranjib; Pal, Suchismita; Biswas, Chaitali; Santra, Sankari; Maji, Sunanda (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Previous studies revealed that the undergraduate medical students have a poor perception about the anaesthesiologists. But, there is paucity of such studies on the postgraduate students. Therefore, this study was conducted to evaluate the perception of the first year post graduate students pursuing anaesthesiology on various professional aspects of this speciality. Methods: A questionnaire-based anonymous cross-sectional survey was conducted on 63 first year postgraduate students of anaesthesiology from seven medical colleges under the West Bengal University of Health Sciences. Data were collected from the students on the day of admission. The questionnaire elicited information on demographic characteristics, functions and health hazards of anaesthesiologists and perception of students about this discipline. The responses were sorted out, coded and analyzed. Results: Involvement in the intra-operative period (84%), critical care (58%), and chronic pain management (40%) were recognized as major functions of an anaesthesiologist. Their role in preoperative and postoperative care was appreciated only by 16% and 18% students respectively. 48% students mentioned ignorance about health hazards associated with practise of anaesthesiology. They considered this discipline stressful, dependent and unrecognised. Conclusions: This study concludes that there exists an inconsistent perception of the roles of anesthesiologists among the new post graduate students. It specifically identifies various potential areas to improve student’s awareness regarding the widespread domain of this discipline. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 67-72